The Relationship Between Non-Financial Compensation Factors with Employees Retention in a Selected Hotel Industry - Nur Fadzillah, Haimi; Rusli, Ahmad; Nur Fatihah, A.B; Siti Mariam, Abdullah; Helmi, Sumilan; Ahmad Sofian, Shminan (UNIMAS Publisher, 2016)
This study aims to determine the relationship between non-financial compensation factors and employees retention in a selected hotel industry. A survey methodology was used in this study. A total of 120 questionnaires were administered to employees who are currently working in the hotel industry. Using the Pearson’s Correlation analysis test, this study analysed the relationship between employees retention and financial compensation factors which include opportunities for training and promo-tion, job challenges, recognition and the working environment. Multiple Linear Re-gression was used to determine the dominant factor that contributes to retention of employees. The results revealed that there was a significant relationship between the factors and employees retention. The results indicated that the working environment is the most dominant factor that contributes to employees retention.